2021
DOI: 10.1002/jemt.23710
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the toxicological effect of silver salt (AgNO3) and silver nanoparticles on Cyprinus carpio synthesized by chemicals and marine algae using scanning electron microscopy

Abstract: The widespread use of silver nanoparticles (AgNPs) results in the unintentional release into the water body. Therefore, understanding of the potentially harmful impacts of AgNPs and Ag‐salt on aquatic animals is a need of time. This study was design to analyze the oxidative stress and histopathological damages in Cyprinus carpio. The synthesis of AgNPs from Halymenia porphyraeformis and by reduction of chemical was done. Nanoparticles were characterized with UV–Visible spectroscopy, SEM, XRD, and FTIR analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The percentage inhibition of invitro toxicity of chemical and biological synthesized Ag/Au NPs was investigated in this study, and it was discovered that biological synthesized both Ag/AuNPs are less toxic, more friendly and biocompatible to human gut microbial community probiotics as compared to chemical synthesized Ag/AuNPs. Our findings corroborate previous research, which found that CH-AgNPs are more toxic than Bio-AgNPs from different plant species and algae [68][69][70][71].…”
Section: Calculation Of Toxic Effectsupporting
confidence: 92%
“…The percentage inhibition of invitro toxicity of chemical and biological synthesized Ag/Au NPs was investigated in this study, and it was discovered that biological synthesized both Ag/AuNPs are less toxic, more friendly and biocompatible to human gut microbial community probiotics as compared to chemical synthesized Ag/AuNPs. Our findings corroborate previous research, which found that CH-AgNPs are more toxic than Bio-AgNPs from different plant species and algae [68][69][70][71].…”
Section: Calculation Of Toxic Effectsupporting
confidence: 92%
“…Similarly, another study has revealed that 7/21 fish were died in 96 hours after exposure to AgNPs (Haghighat et al, 2021). Another recently conducted study has revealed the highest mortality at 1.5 mg/L, in which all common carp fish died in the experiment (Liaqat et al, 2021). In our study case, there was no mortality on the lowest concentration of AgNPs.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that when fish is exposed to various kinds of toxins or toxic environments, that might show influence on fish and their tissue in the sense of bioaccumulation and histopathological alterations (Ibrahim, 2015). The accumulation of silver nanoparticles in gills and liver leads to oxidative stress in fish (Liaqat et al, 2021). Nowadays, nanotechnology is being used to manage fish diseases and being applied for controlling fish diseases (Fuentes‐Valencia et al, 2020), because of its broad anti‐protozoal activity (Allahverdiyev et al, 2011), and anti‐bacterial activity (Kakakhel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the melissopalynological significance of these species, further studies are needed to check the effects of various plant parts extract and powder on animals for its therapeutic potential, hepatic disorders, histology, growth performance and as a supplement in the fish diet by following the previously published literature (Andriamialinirina et al, 2020; Irm et al, 2020; Taj et al, 2020, 2020, 2021). Furthermore, SEM has been recommended to be used in the diverse field of biological sciences (Liaqat et al, 2021; Iqbal et al, 2020; Rubab et al, 2021) for various research purposes.…”
Section: Resultsmentioning
confidence: 99%